Analysis of The Implementation of Inclusive Education Policy in Indonesia : A Literature Review - Nugraha, Redydian Adhitya; Karsidi, Ravik; Rahman, Abdul; Sunardi, Sunardi; Asrowi, Asrowi; Murwaningsih, Tri; Supratiwi, Mahardika (Angstrom Centre of Education, 2024)
This literature review aims to analyze the implementation of inclusive education policies from early childhood education to higher education in Indonesia. Articles were selected through a screening process from 2015-2022. The review was conducted on an online database found on Google Scholar. There were 9 articles reviewed based on the inclusion criteria. Based on the results of the literature review, it was found that inclusive education is an innovative and strategic educational approach to expand access to education for all children with special needs at all levels of education. The inclusive education model has been supported by stakeholders, but in practice there are still various barriers that come from teachers, schools, parents, special education experts and the government. However, the evaluation of inclusive education revealed positive impacts such as increased public awareness and understanding of inclusive education, government efforts to increase the number of educators and improve their quality, and improved accessibility of public facilities for people with disabilities. Recommendations are also provided, especially regarding regulations governing the improvement of educators' competencies, socialization for subject teachers, community support and arrangements for funding the implementation of inclusive education in Indonesia.